SOSIALISASI NILAI-NILAI PENDIDIKAN SEJARAH PERADABAN ISLAM KEPADA MASYARAKAT DESA GIRIYOSO KABUPATEN MUSI RAWAS UNTUK MEMBANGUN MASYARAKAT BERKARAKTER ISLAMI PADA ABAD XXI - Sarkowi Sarkowi; Yeni Asmara (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2021)
Community service that will be carried out is in the form of Disseminating the Educational Values ​​of the History of Islamic Civilization to the Giriyoso Village Community, Musi Rawas Regency to Build a Society with Islamic Character in the XXI Century as an effort to increase understanding and implementation of educational values ​​in the history of Islamic civilization in order to form Islamic character, especially citizens. Giriyoso village to prepare to become a civil society. This service is based on looking at current conditions with the large influence of foreign culture, increasing crime, drugs, juvenile acquaintances, a preventive effort is needed in this case, it is necessary to socialize character education, especially those that lead to Islamic teachings, considering that in Giriyoso village the community is predominantly Muslim. Through this socialization, it is hoped that it can provide information to the participants on the importance of understanding the historical values ​​of Islamic civilization which can be implemented in daily life in the family environment and other social environments so as to be able to create a conducive, safe and peaceful community situation and condition in accordance with demands in civil society. The material delivery system in this socialization activity is to use the lecture method. Furthermore, at the end of the activity there is a question and answer session with participants related to the material that has been delivered by the presenter. This question and answer activity aims to see the extent to which participants understand and are enthusiastic about the activities carried out.